Burnout Syndrome in UK Intensive Care Unit staff: Data from all three Burnout Syndrome domains and across professional groups, genders and ages. (November 2019) - Vincent, Laura; Brindley, Peter G; Highfield, Julie; Innes, Richard; Greig, Paul; Suntharalingam, Ganesh
Introduction: This is the first comprehensive evaluation of Burnout Syndrome across the UK Intensive Care Unit workforce and in all three Burnout Syndrome domains: Emotional Exhaustion, Depersonalisation and lack of Personal Accomplishment. Methods: A questionnaire was emailed to UK Intensive Care Society members, incorporating the 22-item Maslach Burnout Inventory Human Services Survey for medical personnel. Burnout Syndrome domain scores were stratified by 'risk'. Associations with gender, profession and age-group were explored. Results: In total, 996 multi-disciplinary responses were analysed. For Emotional Exhaustion, females scored higher and nurses scored higher than doctors. For Depersonalisation, males and younger respondents scored higher. Conclusion: Approximately one-third of Intensive Care Unit team-members are at 'high-risk' for Burnout Syndrome, though there are important differences according to domain, gender, age-group and profession. This data may encourage a more nuanced understanding of Burnout Syndrome and more personalised strategies for our heterogeneous workforce.